Upconversion luminescence and thermal effects in terbium-ytterbium codoped fluorogermanate glass-ceramic - Gouveia-Neto, A. S.; Bueno, L. A.; Do Nascimento, R. F.; Sundheimer, M. L.; Da Costa, E. B.; Ribeiro, S. J.L. [UNESP]; Messaddeq, Y. [UNESP] (My University, 2009)
Cooperative energy transfer upconversion luminescence is investigated in Tb3+/Yb3+-codoped PbGeO3-PbF 2-CdF2 glass-ceramic and its precursor glass under resonant and off resonance infrared excitation. Bright UV-visible emission signals around 384, 415, 438 nm, and 473-490, 545, 587, and 623 nm are identified as due to the 5D3(5G 6)→7Fj (J=6,5,4) and 5D 4→7Fj (J=6,5,4,3) transitions, respectively, and readily observed. The results indicate that cooperative energy transfer between ytterbium and terbium ions followed by excited state absorption are the dominant upconversion excitation mechanisms involved. Comparison of the upconversion process in a glass-ceramic sample and its glassy precursor revealed that the former present much higher upconversion efficiency. The dependence of the upconversion emission upon pump power, temperature, and doping content is also examined.